Labour Market Performance by Age Groups: A Focus on France - Boulhol, Hervé (OECD Economics Department Working Papers, 2013)
This paper analyses the age structure of employment rates across OECD countries with a focus on France. The statistical contribution of each age group to total unemployment-rate differentials is also computed. An estimate of the sensitivity of age-specific unemployment rates to the economic cycle is provided for OECD countries. France is one of the OECD countries having the highest dispersion of employment rates across age groups. The "within" component of the 15-29 age group accounts for over half of France's total unemployment rate differential with best-performing countries. Youth unemployment rate is especially sensitive to cyclical fluctuations in Spain, Belgium and France